Structural characterization and rheological properties of a galactomannan from Astragalus gombo Bunge seeds harvested in Algerian Sahara. (1st November 2017) - Chouana, T.; Pierre, G.; Vial, C.; Gardarin, C.; Wadouachi, A.; Cailleu, D.; Le Cerf, D.; Boual, Z.; Ould El Hadj, M.D.; Michaud, P.; Delattre, C.
Highlights: High yield polysaccharides extracted from Astragalus gombo seeds. Galactomannan from Astragalus gombo seeds with mannose/galactose = 1.7. High molecular weight galactomannan from Astragalus gombo seeds. Galactomannan with a random coil conformation and pseudo-plastic behaviour. Abstract: A water soluble polysaccharide (WSP) was extracted and purified from Astragalus gombo seeds (Fabaceae) harvested in Septentrional Sahara (Ouargla, Algeria) with a yield of 6.8% (w/w of the dry seed ground). It was characterized by gas chromatography coupled to the mass spectrometry (GC–MS), size exclusion chromatography with Multi-Angle Light Scattering analysis (SEC-MALLS), high–resolution 1 H and 13 C NMR, and rheological measurements. The structural characterization indicated that this WSP fraction is a galactomannan with a mannose/galactose ratio of 1.7 formed by a backbone of β -(1, 4)-d -mannopyranosyl residues (63%) substituted at O-6 position by a single α-galactopyranose residue (37%). SEC-MALLS analysis revealed that this galactomannan has an average molecular mass (Mw) of 1.1 × 10 6 g/mol, an intrinsic viscosity of 860 mL/g and, a random coil conformation structure. Rheological analysis in semi diluted regimes shown pseudo-plastic and viscoelastic behaviour.